2003
DOI: 10.1074/jbc.m306957200
|View full text |Cite
|
Sign up to set email alerts
|

Presenilins Mutated at Asp-257 or Asp-385 Restore Pen-2 Expression and Nicastrin Glycosylation but Remain Catalytically Inactive in the Absence of Wild Type Presenilin

Abstract: The Presenilins are part of the ␥-secretase complex that is involved in the regulated intramembrane proteolysis of amyloid precursor protein and other type I integral membrane proteins. Nicastrin, Pen-2, and Aph1 are the other proteins of this complex. The Presenilins probably contribute the catalytic activity to the protease complex. However, several investigators reported normal A␤-peptide generation in cells expressing Presenilins mutated at the putative catalytic site residue Asp-257, contradicting this hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
99
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 73 publications
(72 reference statements)
17
99
0
Order By: Relevance
“…We found that PS1 complex from cortex of sporadic late-onset AD cases or from pathogenic PS1 point mutations did not have altered apparent mobility in BN/PAGE. This was consistent with study of PS1 complex from transfected SY5Y cells reported here for the artificial PS1 Asp257Ala mutation, and for Asp257 or Asp385 mutations in transfected mouse embryonic fibroblasts [56]. Additional high molecular weight PS1 species of 600 kDa were detected for brain carrying the severe PS1 exon 9 deletion and for SY5Y cells over-expressing this mutation, indicating impairment of normal complex formation in the presence of the mutation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found that PS1 complex from cortex of sporadic late-onset AD cases or from pathogenic PS1 point mutations did not have altered apparent mobility in BN/PAGE. This was consistent with study of PS1 complex from transfected SY5Y cells reported here for the artificial PS1 Asp257Ala mutation, and for Asp257 or Asp385 mutations in transfected mouse embryonic fibroblasts [56]. Additional high molecular weight PS1 species of 600 kDa were detected for brain carrying the severe PS1 exon 9 deletion and for SY5Y cells over-expressing this mutation, indicating impairment of normal complex formation in the presence of the mutation.…”
Section: Discussionsupporting
confidence: 78%
“…Other recent studies have also utilized BN/PAGE for analysis of PS complexes. DDM at 0.5% has been recently reported independently to preserve PS complex integrity in BN/PAGE with reports of complex size from 440 to 600 kDa [12,13,42,55,56]. Digitonin (1%) and BN/ PAGE produced PS1 complex mobility of 250-270 kDa in cells over-expressing the four main constituents of the c-secretase complex [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation or genetic ablation of a given component typically causes a decrease in the level of the other components and/or in the maturation and trafficking of the ␥-secretase complex to its functional sites (6, 8 -18). An exception is APH-1, which is stable in the absence of PS (13,19,20). Increased ␥-secretase complex formation and activity have been observed when all four ␥-secretase complex components are overexpressed in cultured Drosophila and mammalian cells (17,21,22).…”
mentioning
confidence: 99%
“…The mechanism underlying this effect remains unknown, although it has been proposed that heteromeric macromolecular complexes containing presenilins mediate ␥-secretase cleavage of the amyloid ␤-precursor protein. Using a random mutagenesis screen of presenilin-1 (PS1) for PS1 endoproteolysis-impairing mutations, we identified five unique mutants, including R278I-PS1 and L435H-PS1, that exclusively generated a high level of A␤ 43 , but did not support physiological PS1 endoproteolysis or A␤ 40 generation. These mutants did not measurably alter the molecular size or subcellular localization of PS1 complexes.…”
mentioning
confidence: 99%